HUBUNGAN INDEKS MASSA TUBUH DENGAN JUMLAH LEVEL YANG TERKENA PADA STENOSIS KANALIS SPINALIS LUMBALIS DI RSPAD GATOT SOEBROTO JAKARTA TAHUN 2019-2021 - Ihsan Febrianto Rahman, (2023)
Lumbar spinal stenosis was a narrowing that occurs in the spinal canal with predilection in the lumbar region. A high body mass index have a high risk of experiencing lumbar spinal canal stenosis. Obesity is related to the progression of the number of affected levels, the emergence of multilevel stenosis has been a high risk for reoperation. Data from the Gatot Soebroto Army Central Hospital Jakarta found 46 cases during 2020 andl increasing to 67 cases in 2021. Even so, the evidence to support body mass index with the number of levels affected is still minimal. This study aims to determine the relationship between body mass index and the number of levels affected in lumbar spinal stenosis. This research is a secondary research in the form of an retrospective observational analytic study with a cross-sectional approach to 80 patients with lumbar spinal canal stenosis at Gatot Soebroto Army Central Hospital Jakarta Period 2019-2021. The sampling technique used is the consecutive sampling method. All samples that met the inclusion and exclusion criteria were included in thejstudy. By using the Chi-Square test with the SPSS computer program version 24.0, a P value=0.006 (p <0.05) was obtained and an odds ratio value of 0.257. In conclusion, there is a relationship between body mass index and the number of levels affected in lumbar spinal canal stenosis at Gatot Soebroto Army Hospital, Jakarta. Keywords: Lumbar Spinal Stenosis, Multilevel Stenosis, Single Level Stenosis, Body Mass Index